Preparation and Performance Research of Gypsum Based Phase Change Materials - Sun, Daosheng; Ge, Wenbin; Wang, Aiguo; Sun, Peng; Guo, Lin (Asian Journal of Chemistry, 2014)
Expanded perlite and ceramsite were used as carriers, expanded perlite-paraffin (EP) and ceramsite-paraffin (CP) composite phase change materials (PCMs) were prepared by vacuum impregnation method and the optimal adsorbance were tested; and then gypsum based PCMs were prepared. The influences of two kinds of composite PCMs on thermal performance and mechanical performance of gypsum based materials were studied. The results showed that with the increase of the proportion of composite PCMs, heating and cooling rate of gypsum based PCMs were slowed down and it took longer to reach equilibrium temperature. Thermal inertia was increased by addition of composite PCMs; The composite effect of expanded perlite-paraffin and gypsum was better than ceramsite-paraffin and gypsum. The compressive strength of the sample with 20 % of expanded perlite-paraffin was 12.7 % higher than that of the sample with expanded perlite in the same volume of expanded perlite-paraffin.